Managing Uncertainty in Organizational Communication - Kramer, Michael W. (Mahwah, N.J. : Lawrence Erlbaum Associates Publishers, 2004)
"Managing Uncertainty in Organizational Communication will assist readers in understanding and researching uncertainty in communication, which will encourage additional changes and improvements to the model. It will be of primary interest to scholars, researchers, and practitioners in organizational, interpersonal, and group communication, and will also be valuable in graduate courses in these areas."--BOOK JACKET.
1. Introduction and Rationale -- 2. Uncertainty Reduction Theory in Interpersonal Contexts -- 3. Uncertainty in Group and Organizational Contexts -- 4. A Theory of Managing Uncertainty: A New Model -- 5. Cognitive and Behavioral Processes for Managing Uncertainty: A Qualitative Study of Car Salespeople -- 6. The Influence of Competing Motives on Managing Uncertainty: Responses to Organizational Scenarios -- 7. A Textual Analysis of Managing Uncertainty: A Reanalysis of the Lucille Burger Story -- 8. Implications and Conclusions.
Includes bibliographical references (p. 219-230) and indexes.
Keywords: Communication in organizations; Uncertainty (Information theory)